2020
DOI: 10.3390/pharmaceutics12111091
|View full text |Cite
|
Sign up to set email alerts
|

Quality-by-Design Approach for the Development of Nano-Sized Tea Tree Oil Formulation-Impregnated Biocompatible Gel with Antimicrobial Properties

Abstract: Despite the promising properties of tea tree oil (TTO) as potential therapeutics for several superficial skin conditions, certain limitations such as physical instability and skin irritation have restricted its widespread use. This study focuses on developing a rationally designed lipid-based nanoformulation (TTO-LNF) in accordance with the US Food and Drug Administration standard using a well-recognized quality-by-design (QbD) approach. Using a mixture experimental design, TTO-LNF has been optimized with 5% T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…There was no significant difference between GP (3) and GP (4) at all time intervals revealing that TTO exerted comparable antimicrobial efficacy to clindamycin hydrochloride against skin transient flora. These results agree with Muta et al (2020) , who found that TTO lipid-based nanoformulation (5% TTO) exhibited bitter antibacterial activity against S. epidermidis than kanamycin.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…There was no significant difference between GP (3) and GP (4) at all time intervals revealing that TTO exerted comparable antimicrobial efficacy to clindamycin hydrochloride against skin transient flora. These results agree with Muta et al (2020) , who found that TTO lipid-based nanoformulation (5% TTO) exhibited bitter antibacterial activity against S. epidermidis than kanamycin.
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…The instrument works on the principle of dynamic light scattering (DLS). s-SNEDDS of 100 mg were diluted with 90 mL of deionized water, sonicated for 50 s and left undisturbed for 2 h. Then, the evaluation of droplet size and PDI of the collected samples was performed at 25 ± 2 °C with a constant refractive index of 1.471 [ 40 ]. All the observations were carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…A UV spectrophotometer was used to determine the percentage of transmittance of the s-SNEDDS. Then, 100 mg of s-SNEDDS were diluted with 90 mL of deionized water, sonicated for 50 s and left undisturbed for 2 h. Next, the percentage of transmittance of the samples were measured at 510 nm with deionized water as blank [ 40 ]. All the observations were carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NEO has been investigated as a permeation enhancer for transdermal and cutaneous drug delivery of estradiol via gel formulations [18,19]. Various topical NE-based formulations of similar essential oils, such as tea tree oil, have been investigated for biological evaluation [20][21][22][23]. Topical NEs of other essential oils, such as eucalyptus essential oil, celery essential oil, psoralen, lemongrass essential oil, and babchi essential oil, have also been studied in the literature [12,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%